El cabildo y la universidad. Las primeras canonjías de oficio en México (1598-1616) - Pérez, Leticia (2012)
This article deals with the interest groups which were spawned by the creation of the first canonries for the Mexican cathedral. The article shows that it was the royal university which gave rise to these interest groups because it viewed those canonries as future occupations for its students and a political means for its own institutional consolidation. Likewise, the text brings out the fact that the cathedral chapter initially opposed the creation of these prebends arguing that they altered the traditional forms of promotion of canons and increased competition, opening the doors to lettered Creoles and brought about the direct intervention of bishops and viceroys in the election of the people that would make up the chapter.